Soil Degradation Due to Over Exploitative Human Effort - Dhir, R P (Annals of Arid Zone, 2016)
In over two thousand year old history of human settlement in western Rajasthan,the whole area appears to have been well populated and politically organised by the 8th century A.D. From then onwards through Mediaeval and late Mediaeval periods there has been only a slow growth of population under a dominantly pastoral land use. However, from the third decade of present century, there had been a continuous sharp increase in population with a parallel increase in incidence of arable farming. This human activity is manifested in increased component of loose sand and hummock formation with some loss in productivity in form of reduced fertility and poor stand of crops.